Factors Affecting Accountability of Village Fund Management through Implementation of the Village Financial System (SISKEUDES) - Icuk Rangga Bawono; Anasti Dwi Martantya Kinasih; Apriani Kartika Rahayu (Journal of Accounting and Investment, 2020)
Research aims: This study has pupose to analyze the factors that consist of role and competence of village officials, village financial system implementation on the accountability of village fund management. In addition, this research examine  application of village financial system as intervening variable.Design/Methodology/Approach: The quantitative method used in this study with a survey approach, by distribute questionnaire to village secretaries and heads of village financial affairs as respondents that spread in 182 village on Banyumas Regency, Central Java. From distributed questionnaire, totally 120 that can be processed with Partial Least Square approach.Research Finding: The result found that role of village officials, competence of village officials, and application of village financial system partially significant on the accountability of village fund management. The result also confirmed that role and competence of village officials partially significant on the accountability of village fund management through application of village financial system. This research construct able influence 77% of the accountability of village fund management variable.Theoretical Contribution/Originality: This research confirm implementation village financial system could mediate relationship between role and competence of village officials on the accountability of village fund management in study of governmental.Practitioner/Policy implication: The village government needs to encourage participation and competence of village officials in managing village fund management. Train officials about village financial system also needed to obtain better accountability about village management funds.Research limitation/Implication: This research was only undertaken in the scope of Banyumas regency. Therefore, the generalization ability of this study is limited.